The Feasibility of Video Tutorial Learning Media for Batik in Arts and Culture Subjects in Vocational High Schools (SMK) - Yulia Khoirun Nisa; Godham Eko Saputro (Universitas Negeri Semarang, 2026)
Learning batik in the Arts and Culture subject in Vocational High Schools (SMK) still faces the problem of low student understanding, which is caused by limited media and methods of delivering material orally so that the learning practice process is less effective. This study aims to test the feasibility of learning media in the form of a batik tutorial video for arts and culture subjects. This study uses a research and development method with a 4-D model that includes the stages of defining, designing, developing, and disseminating. The subjects of this study consisted of three media experts and three material experts who served as validators. The data collection technique for this study used a feasibility assessment sheet, while data analysis was carried out using a quantitative descriptive approach through calculating the average score. The validation results by media experts showed an average score of 3.62 which is included in the